One-dimensional analysis of underground water using geoelectric methods - Usman Malik; Defrianto Defrianto; Zulfa Zulfa; Yohanes Dwi Saputra; Juandi Muhammad (Science, Technology, and Communication Journal, 2023)
The regional development issues in Tambang Kampar District that are most important to solve are environmental issues related to surface water potential and limited clean water. Environmental potential through good environmental management can become potential natural resources that can be utilized to support the regional economic sector. Groundwater potential needs to be studied and interpreted in the matrix of groundwater resource management through geophysical studies, namely by using the geoelectric method. This matrix will be able to provide solutions to environmental problems with the potential for fresh water in Tambang District, Kampar, thereby supporting economic growth in terms of meeting water needs. The material that is the object of research is underground water, and the aspects of research that will be studied include clean water exploration and environmentally friendly management patterns of potential underground water resources. The research location is Tambang District, Kampar, Riau Province. The targeted finding is an environmental management model of potential underground water resources in Tambang Kampar District using the Schlumberger rule geoelectrical method. Fundamental contributions to a field of science are geophysics and environmental science disciplines related to groundwater availability.